Red book 2018-2021: Report of the Committee on Infectious Diseases - Kimberlin, D. W. David W. (American Academy of Pediatrics, 2018)
Extending an 8-decade tradition of excellence, Red Book provides page after page of the latest evidence-based recommendations for the prevention and management of more than 200 infectious diseases in infants, children, and adolescents. The 31st edition provides evidence-based guidance on pediatric infections and vaccinations based on the recommendations of the American Academy of Pediatrics (AAP) Committee on Infectious Diseases and AAP policy, as well as the combined expertise of the Centers for Disease Control and Prevention, the US Food and Drug Administration, and hundreds of physician contributors. In all, more than 1.000 hands have touched the Red Book prior to its publication! The Red Book is like having your own personal infectious disease consultant available to you, on your bookshelf, at all times.